2021
DOI: 10.1039/d1nr00530h
|View full text |Cite
|
Sign up to set email alerts
|

Lipid nanotubes as an organic template for the fabrication of carbon nanostructures by pyrolysis

Abstract: We demonstrate the fabrication of pyrolytic carbon nanostructures through pyrolysis of lipid nanotube templates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…42 Other spectral mapping based on scanning microscopy methods, such as infrared scattering scanning near-field optical microscopy (IR-s-SNOM) 43,44 and tipenhanced Raman spectroscopy (TERS), may be an alternative tool. 45 We found that each blue structure undergoes a unique path to diverse types of red structure, where a pattern, e.g., a certain blue structure prefers to transform into a certain red structure, was detected. The result implies that the stimulus (heat, in this work) leaves a fingerprint to the PDA blue-to-red transition pathways.…”
Section: Conflicts Of Interestmentioning
confidence: 77%
“…42 Other spectral mapping based on scanning microscopy methods, such as infrared scattering scanning near-field optical microscopy (IR-s-SNOM) 43,44 and tipenhanced Raman spectroscopy (TERS), may be an alternative tool. 45 We found that each blue structure undergoes a unique path to diverse types of red structure, where a pattern, e.g., a certain blue structure prefers to transform into a certain red structure, was detected. The result implies that the stimulus (heat, in this work) leaves a fingerprint to the PDA blue-to-red transition pathways.…”
Section: Conflicts Of Interestmentioning
confidence: 77%